1967
DOI: 10.1139/m67-022
|View full text |Cite
|
Sign up to set email alerts
|

The MICROBIAL PRODUCTION AND SOME CHARACTERISTICS OF Δ-Carboxymethyl-Α-Hydroxymuconic SEMIALDEHYDE

Abstract: Suspensions of Pseudomonas grown on phenylacetic acid oxidized 3,4-dihydroxy-phenylacetic acid to δ-carboxymethyl-α-hydroxymuconic semialdehyde. The compound was characterized by conversion to 2,5-pyridine dicarboxylic acid. The results show that cleavage of the aromatic ring occurs between carbons 2 and 3. δ-Carboxymethyl-α-hydroxymuconic semialdehyde is relatively unstable. Maximum absorption of the compound is obtained in acid at 318 mμ and in alkali at 380 mμ. The ratio of optical densities (380/318) is 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…These spectra are identical with those of 2-hydroxy-5-carboxymethylmuconate semialdehyde (Adachi et al, 1964), which is formed by the meta-cleavage of 3,4-dihydroxyphenylacetate (Fig. 3) (Blackley et al, 1967;Sparnins et al, 1974) by the enzyme 3,4-dihydroxyphenylacetate 2,3-dioxygenase (EC 1.13.11.15) (Ono-kamimoto, 1973;Sparnins et al, 1974). Table 2 shows the activities of this enzyme in crude extracts of S. marcescens…”
Section: R E S U L T Ssupporting
confidence: 55%
See 3 more Smart Citations
“…These spectra are identical with those of 2-hydroxy-5-carboxymethylmuconate semialdehyde (Adachi et al, 1964), which is formed by the meta-cleavage of 3,4-dihydroxyphenylacetate (Fig. 3) (Blackley et al, 1967;Sparnins et al, 1974) by the enzyme 3,4-dihydroxyphenylacetate 2,3-dioxygenase (EC 1.13.11.15) (Ono-kamimoto, 1973;Sparnins et al, 1974). Table 2 shows the activities of this enzyme in crude extracts of S. marcescens…”
Section: R E S U L T Ssupporting
confidence: 55%
“…Sugar fermentation tests, the ability to grow on different carbon and energy sources and other typical enterobacterial tests (Blazevic, 1980;Farmer et al, 1985;Grimont & Grimont, 1984) demonstrated that strains CY429 and CY918 belong to S. marcescens. Growth on tyrosine as a sole carbw and energy source is a property which characterizes all strains of the genus Serratia studied by Grimont & Grimont (1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have shown that Pseudomonas putida (strain U) can grow very efficiently in a minimal defined medium containing phenylacetic acid (PA) as the sole carbon source (26). Under aerobic conditions, this strain, unlike other Pseudomonas strains which also can use PA as an energy source (5,6,8,35), degraded this aromatic compound through a probably new catabolic pathway which involves, as a first step, the activation of PA to its coenzyme A (CoA) derivative (phenylacetyl-CoA [PA-CoA]) (23)(24)(25)(26)35). …”
mentioning
confidence: 99%